Screening of Degenerative Diseases and Quality of Life among Elderly People in Posyandu Lansia Medan Amplas Sub-Districts, Medan - Juliandi Harahap; Lita Sri Andayani (Syiah Kuala University, 2015)
The number of elderly people in Indonesia from year to year is increasing in line with increasing life expectancy. The number of elderly people reached 7.56% of the population. Certainly, the increase in the elderly population will be followed by an increased risk for the elderly to suffer from degenerative diseases. This study aimed to assess the role of degenerative disease screening and health counseling to the quality of life of the elderly in the health post (Posyandu Lansia). This study was a descriptive analytic with prospective approach by assessing 100 elderly people. Screenings done for examination of blood pressure, blood sugar level, cholesterol level, uric acid level, and urine protein. Assessment of quality of life done by using questionnaire of WHOQOL. The elderly in Posyandu Lansia were educated in accordance with the results of the screening and followed up for 4 months. Screening results showed that most elderly people had high blood pressure (89% had high systolic blood pressure and 70% had high diastolic blood pressure). As much as 55% of elderly people had cholesterol levels ≥ 200 mg/dl, while blood sugar levels as ≥ 200 mg/dl were 20% of the elderly and only 20% of respondents who had uric acid levels that exceed normal limits (8,5mg/dl). As many as 13 of respondents indicated a positive result in urine protein. Assessment of the quality of life of elderly based on the score at first examination obtained a mean of 88.26 ± 9.1. Regarding general health status, 21% of elderly felt less satisfied, 47% declared that their health status in normal conditions and 32% felt satisfied with their current health status. The score of quality of life after receiving counseling, obtained a mean of 89.31 ± 7.8. Assessment of general health status showed only 11% of elderly declared unsatisfactory health status. Result of t test showed that there was a significant difference between score of quality of life before and after screening degenerative diseases (p0.05). Screening of degenerative diseases showed a majority of the elderly had a potential risk to suffer from degenerative diseases. Prevention through screening and health counseling particularly in Posyandu Lansia can reduce morbidity and mortality in elderly, and therefore it will improve quality of life for the elderly